Chronic opioid use in females with cholelithiasis due to delayed surgeries in government hospitals - Farooq, Muhammad Rizwan (Journal of the Pakistan Medical Association, 2026)
Dear Editor, Cholelithiasis is one of the most prevalent surgical conditions in Pakistan, with females disproportionately affected due to hormonal and metabolic factors. [1] Laparoscopic cholecystectomy remains the treatment of choice; however, in government hospitals, surgical waiting lists are often prolonged, sometimes exceeding a year.[2] During this period, women frequently experience recurrent biliary colic and present to emergency departments, where opioids are commonly prescribed for pain control. Although effective for acute relief, repeated opioid exposure increases the risk of chronic use and dependence.[3] Women are particularly vulnerable due to biological predisposition and the added burden of social stigma associated with substance dependence in this demographic. [4] This preventable complication highlights a gap in both surgical services and safe pain management practices. Practical measures are urgently needed. Increasing surgical capacity, introducing dedicated gallstone surgery lists, and optimising operating theatre utilisation could significantly reduce waiting times. Referral of stable patients to peripheral centres may also help distribute the surgical load. At the same time, physicians must be sensitised to the risks of prolonged opioid prescribing and encouraged to adopt multimodal pain management strategies, including non-opioid alternatives.[5] Development of national guidelines on perioperative pain management for gallstone disease would further safeguard against unnecessary opioid exposure. Implementing these stepswill reduce suffering among female patients, minimize avoidable opioid dependence, and improve the overall quality of surgical care in Pakistan.